Integrated application of rehabilitation means in circannian training cycle of highly-qualified Greco-Roman style wrestlers - Kuznetsov, A. S.; Kuznetsova, Z. M. (The Russian Journal of Physical Education and Sport, 2017)
Rivalry level increase during competitions and also the level of stability increase in such a difficult coordination kind of sport, as Greco-Roman wrestling, cause the necessity to search for new approaches to the training system and process of wrestlers. In this connection the problem of all sides of training improvement stays very urgent, as sports result depends on them. The training process intensification without any harm to sportsmen`s health is possible in case of a rational training lessons organization and different rehabilitation means use. In this connection it is important to study the aspects, connected with different rehabilitation means use during the process of sports training among wrestlers, which provide working capacity support. Material. The effectiveness of integrated use of rehabilitation means in circannian training cycle of highly-qualified Greco-Roman style wrestlers. Research methods: scientific and methodical literature analysis and summarizing, modeling, mathematical statistics methods. Results. It was revealed that the structure of rehabilitation means use in circannian training cycle of highly-qualified Greco-Roman style wrestlers should be realized taking into account the following factors: a wrestler`s weight category; the type of rehabilitation means influence; characteristics of rehabilitation means use; the peculiarities of a gradual use of different rehabilitation means; individual characteristics of a wrestler; the objectives of the training period and stage. The result of an integrated use of rehabilitation means in training highly-qualified Greco-Roman style wrestlers is competitive activity effectiveness increase and traumatism prevention. Conclusion. The methodology was tested during the pedagogical experiment, which conditioned a detailed specification of all parts of an integrated use of rehabilitation means in circannian training cycle of highly-qualified Greco-Roman style wrestlers, taking into account their weight categories.